(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
This study include the evaluation of natural radionuclide levels in food samples included (canned beans and canned meat) collected from local markets in Hilla city, conducted spectral measurements using the reagent system sodium activated iodide thallium NaI (Tl), which nominally (3× 3). The quality activity for Uranium 238U, Thorium 232Th, and Potassium 40K in the beans samples is between) 2.870±0.50) Bq/kg to (34.899±1.79) Bq/kg with an average (14.779±1.05 (Bq/kg and (4.701±0.76(Bq/kg to (36.593±1.89 (Bq/kg (with an average (16.517±1.18 (Bq/kg and (131.329±4.08) to (690.703±8.58)Bq/kg with an average (327.915±5.56( Bq/kg. Also We are found that the quality activity for Uranium 238U, Thorium 232Th, and Potassium 40K in the meat samples is between (0.733±0.26 )Bq/kg to (1.717±0.37) Bq/kg with an average (1.519±0.364) Bq/kg and between (2.141±0.46) Bq/kg to )13.830±1.15) Bq/kg with an average(0,69±6,6202) Bq/kg and between( 31.551±1.77) Bq/kg to Bq/kg with an average (126,89±5.22) (126,89±3,364)Bq/kg .Also, The Radium Equivalent is calculated and ranged between (20.794)Bq/kg to (122.601)Bq/kg with an average (63,649) Bq/kg for beans samples and between (6.224)Bq/kg to (42.784)Bq/kg with an average (20.756)Bq/kg for meat samples . the internal risk coefficient is calculated and its value ranged between ( 0.019)Bq/kg to (0.119) Bq/kg with an average (0.0598)Bq/kg for meat samples and between (0.067) Bq/kg to (0.425) Bq/kg with an average(0.212 (Bq/kg for beans samples. The results comparison with internationally and it is found that the levels of radiation for the meat samples within the permissible limits globally. In the beans that clear some samples contain high concentration of Uranium 238U and Potassium 40K also, absorbed that was increase in the annual effective does in three samples of beans ,therefore most decrease from eating the beans because its danger in long time.